2019
DOI: 10.3390/s19051241
|View full text |Cite
|
Sign up to set email alerts
|

Portable Sensors Add Reliable Kinematic Measures to the Assessment of Upper Extremity Function

Abstract: Ordinal scales with low resolution are used to assess arm function in clinic. These scales may be improved by adding objective kinematic measures. The aim was to analyze within-subject, inter-rater and overall reliability (i.e., including within-subject and inter-rater reliability) and check the system’s validity of kinematic measures from inertial sensors for two such protocols on one person. Twenty healthy volunteers repeatedly performed two tasks, finger-to-nose and drinking, during two test sessions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…A problem with this method is that it is only available to specialized centers due to high costs and requirements of expert operation. Alternatively, portable systems based on inertial measurement units (IMUs) show promising results for different clinical applications assessing gait and lower limb joint angles [25,26,27,28,29,30,31]. A recent review compared IMU systems to standard systems used in gait analysis [31] and concluded that portable IMU systems can be used for this purpose in clinical settings with good reliability.…”
Section: Introductionmentioning
confidence: 99%
“…A problem with this method is that it is only available to specialized centers due to high costs and requirements of expert operation. Alternatively, portable systems based on inertial measurement units (IMUs) show promising results for different clinical applications assessing gait and lower limb joint angles [25,26,27,28,29,30,31]. A recent review compared IMU systems to standard systems used in gait analysis [31] and concluded that portable IMU systems can be used for this purpose in clinical settings with good reliability.…”
Section: Introductionmentioning
confidence: 99%
“…We here assess the device through an experiment involving 10 users in an online trajectory-tracking task in VR, showing that it affords an average precision of 0.66 cm during a precision task and 6.33 cm while tracking a target moving along a prerecorded trajectory, when tested in the full peri-personal space of a user. These values are much larger than the absolute precision of the VR system employed in the experiment, which appears reasonable, given the pointing precision attainable by a human being [14].Potential applications of this device, not limited to rehabilitation robotics [15] and discussed in detail at the end of this paper, are endless.…”
mentioning
confidence: 65%
“…Potential applications of this device, not limited to rehabilitation robotics [15] and discussed in detail at the end of this paper, are endless.…”
mentioning
confidence: 99%
“…The results of the current study are only applicable for the kinematic motion capture systems using multiple optoelectronic cameras. The results seem, however, to be similar even when the kinematics are collected by other systems, such as Kinect camera or inertial sensors (32,33). This is promising, taking the constant push from users (clinicians, researchers and patients) to make movement analysis more readily available with systems that can operate outside the lab.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…A study using a virtual reality gaming Kinect system showed that 2 to 5 trials during reaching were needed to achieve performance stability in movement time and elbow and shoulder range of motion (32). Additionally, when using an inertial sensor system, comparable results of 3 trials was considered enough to reach acceptable levels of reliability for movement time and shoulder and elbow range of motion during a drinking task in non-disabled participants (33). These results con rm that for most of the kinematic variables a set of 3 trials would be su cient.…”
Section: Number Of Trials Needed To Reach Good Performance Stabilitymentioning
confidence: 99%